GROWTH PERFORMANCE AND HAEMATOLOGICAL CHARACTERISTICS OF WEANLING WISTAR RATS FED CAELIFERA SUPPLEMENTED DIETS (FUDMA JOURNAL OF SCIENCES, 2023)
This research was conducted to determine the growth performance and haematological status of rats fed with Caelifera-supplemented weaning diets. Twenty four (24) weanling albino rats with mean weight of 39.27g ± 0.3g were divided into four (4) groups of equal average weight and randomly assigned to four experimental diets. Diet C (control) was Nestle wheat Cerelac. Diet A contained Rheum australe (45%), Caelifera (12.5%) Daucus carota (10%), Glycine max (30%), and sucrose (2.5%) while diets W and M respectively contained Triticum aestivum and Pennisetum glaucum instead of Rheum austral. The rats were fed ad libitum for six weeks. Proximate compositions of the diets, growth and haematological parameters were determined using standard methods. The results revealed that ash content of Diet A (0.630 ± 0.04), Diet W (0.287±0.01), and Diet M (0.490 ± 0.03) were significantly (p
Keywords: Caelifera-supplement; complementary